2013
DOI: 10.1371/journal.pone.0054350
|View full text |Cite
|
Sign up to set email alerts
|

Passive Exercise of the Hind Limbs after Complete Thoracic Transection of the Spinal Cord Promotes Cortical Reorganization

Abstract: Physical exercise promotes neural plasticity in the brain of healthy subjects and modulates pathophysiological neural plasticity after sensorimotor loss, but the mechanisms of this action are not fully understood. After spinal cord injury, cortical reorganization can be maximized by exercising the non-affected body or the residual functions of the affected body. However, exercise per se also produces systemic changes – such as increased cardiovascular fitness, improved circulation and neuroendocrine changes – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 97 publications
4
46
0
Order By: Relevance
“…This is similar to the early work of Olds (1965) andFetz (1969) showing neurons can be trained to modify their activity for a reward (for review, seeGanguly and Carmena, 2009;Manohar et al, 2012;Ganguly et al, 2011 for more recent studies in BMIs). However, after SCI there is an upregulation of proteins associated with plasticity (Endo et al, 2007;Graziano et al, 2013) and, therefore, this training is occurring in a more plastic state, likely supporting the functional reorganization.…”
Section: Complete Sci Transiently Disrupts Scaling Mechanismmentioning
confidence: 99%
“…This is similar to the early work of Olds (1965) andFetz (1969) showing neurons can be trained to modify their activity for a reward (for review, seeGanguly and Carmena, 2009;Manohar et al, 2012;Ganguly et al, 2011 for more recent studies in BMIs). However, after SCI there is an upregulation of proteins associated with plasticity (Endo et al, 2007;Graziano et al, 2013) and, therefore, this training is occurring in a more plastic state, likely supporting the functional reorganization.…”
Section: Complete Sci Transiently Disrupts Scaling Mechanismmentioning
confidence: 99%
“…The results illustrated in this review are consistent with the findings of other experimental studies, demonstrating that passive training after spinal cord transection is sufficient to increase the neural responsiveness of the deafferented hindpaw cortex to tactile stimuli delivered to the forepaw/forelimb under deep anesthesia. 33 The authors found that the level of proteins associated with plasticity, in particular BDNF and adenylate cyclase type 1, increased in the somatosensory cortex of adult rats with complete thoracic transection that received passive hindlimb bike exercise compared to transected rats that received sham exercise. Electrophysiological techniques revealed that neurons in the deafferented hindlimb cortex increased their responsiveness to tactile stimuli delivered to the forelimb in transected animals that received PC exercise compared to transected animals that received sham exercise.…”
Section: Discussionmentioning
confidence: 99%
“…33 PC may thus represent a low-cost therapeutic intervention with demonstrable motor, sensory and cardiovascular benefits. The results illustrated in this review are consistent with the findings of other experimental studies, demonstrating that passive training after spinal cord transection is sufficient to increase the neural responsiveness of the deafferented hindpaw cortex to tactile stimuli delivered to the forepaw/forelimb under deep anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the relationships between changes in tuning properties and plasticity, it is feasible to propose new paradigms that combine BMI with other techniques that modulate cortical plasticity at a more global level, such as pharmacological interventions (Maya Vetencourt et al, 2008;Ganzer et al, 2013), exercise (Cotman et al, 2007;Graziano et al, 2013), or electromagnetic neuromodulation with either direct current stimulation (Bindman et al, 1964;Má rquez-Ruiz et al, 2012;Filmer et al, 2014) or static magnetic field stimulation (Oliviero et al, 2011;Aguila et al, 2014). With these combined paradigms, the causality of BMI could be exploited to clarify the mechanisms by which interventions inducing changes in plasticity at a broad population level can affect tuning properties at the cellular level and ultimately behavior.…”
Section: Bmi To Study Plasticitymentioning
confidence: 99%